Pengaruh Kompensasi Dan Benefit Terhadap Kepuasan Kerja Karyawan PT Pegadaian UPC Sei Sikambing - Nur Hafiz, Khairun; Sitepu, M.Bayu Permana; Riskiah, Putri; Arifin, Daud (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2026)
This study is motivated by the importance of employee job satisfaction in improving organizational effectiveness, particularly at PT Pegadaian UPC Sei Sikambing. Employee job satisfaction is influenced by several factors, including compensation and benefits provided by the company. This study aims to analyze the effect of compensation and benefits on employee job satisfaction. The research method used is a quantitative approach with an associative research design. The population in this study consists of all employees of PT Pegadaian UPC Sei Sikambing, using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The results show that compensation has a positive and significant effect on employee job satisfaction with a significance value of 0.002. Benefits also have a positive and significant effect on job satisfaction with a significance value of 0.006. Simultaneously, compensation and benefits have a significant effect on employee job satisfaction with a significance value of 0.000. The coefficient of determination value of 0.638 indicates that 63.8% of the variation in job satisfaction is explained by these two variables. Based on the findings, it can be concluded that compensation and benefits are important factors in improving employee job satisfaction. Therefore, the company is recommended to continuously improve a fair compensation system and strengthen employee benefit programs in order to create optimal job satisfaction.